Optimization of CRISPR–Cas system for clinical cancer therapy - Xiang Meng; Tian‐gang Wu; Qiu‐yue Lou; Kai‐yuan Niu; Lei Jiang; Qing‐zhong Xiao; Tao Xu; Lei Zhang (Bioengineering & Translational Medicine, 2023)
Abstract Cancer is a genetic disease caused by alterations in genome and epigenome and is one of the leading causes for death worldwide. The exploration of disease development and therapeutic strategies at the genetic level have become the key to the treatment of cancer and other genetic diseases. The functional analysis of genes and mutations has been slow and laborious. Therefore, there is an urgent need for alternative approaches to improve the current status of cancer research. Gene editing technologies provide technical support for efficient gene disruption and modification in vivo and in vitro, in particular the use of clustered regularly interspaced short palindromic repeats (CRISPR)–Cas systems. Currently, the applications of CRISPR–Cas systems in cancer rely on different Cas effector proteins and the design of guide RNAs. Furthermore, effective vector delivery must be met for the CRISPR–Cas systems to enter human clinical trials. In this review article, we describe the mechanism of the CRISPR–Cas systems and highlight the applications of class II Cas effector proteins. We also propose a synthetic biology approach to modify the CRISPR–Cas systems, and summarize various delivery approaches facilitating the clinical application of the CRISPR–Cas systems. By modifying the CRISPR–Cas system and optimizing its in vivo delivery, promising and effective treatments for cancers using the CRISPR–Cas system are emerging.